(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study provides a comprehensive analysis of the economic impacts of eco-tourism in Uzbekistan’s rural regions, weaving together the roles of digital marketing, electronic word-of-mouth (EWOM), and synergies with pilgrimage tourism. Drawing on extensive 2023-2024 data, it examines income generation, employment opportunities, and economic diversification as pivotal drivers for reducing rural poverty and underemployment. Employing a mixed-methods approach—surveys, interviews, and structural equation modeling (SEM)—the research uncovers a strong foundation for sustainable economic growth, tempered by significant challenges in infrastructure, funding, and marketing. These findings aim to guide Uzbekistan’s “Tourism Development Strategy 2030,” which targets 9 million annual visitors by 2026, offering actionable insights for policymakers and stakeholders.